Power Up Your Classroom : Reimagine Learning Through Gameplay - Blass, Lindsey; Tolnai, Cate (Book collections on Project MUSE., 2019)
By the time Lindsey Blass and Cate Tolnai's paths crossed, they each knew their own "why" for leveraging the power of gameplay in learning. Both had taken a path from teacher to coach to central/county office roles focused on innovative learning design, all while noticing three trends that extended beyond their classrooms: students who weren't able to own and connect to their learning experience became disengaged; there was a general fear of failure among students and teachers; and teachers were perplexed at how to design engaging learning experiences that fostered student choice and celebrated failure as an opportunity for iteration. Together, they began to ask ... what if? What if we designed learning experiences that leveraged the power of gameplay to create more motivated learners? What if we modeled this type of learning with educators so they could experience the impact firsthand and spread the excitement and innovation in their classrooms? What if learning was fun for both students and teachers? With a uniquely engaging style, Power Up Your Classroom helps educators understand the benefits of gamification and game-based learning, and empowers them to design learning experiences that leverage gameplay to increase motivation and engagement, and build classroom community.